Effect of television viewing on food and nutrient intake among adolescents - Ramos, E (2013)
Objective: Among the behaviors associated with food intake, exposure to television is particularly important given the number of adolescents exposed. Also, increased time spent watching television has been associated with physical inactivity and with less desirable dietary intake among adolescents. The aim of this study was to examine the association between television viewing and dietary intake among 13-y-old adolescents. Methods: A cross-sectional evaluation was carried out in the 2003–2004 school year, including adolescents born in 1990 and enrolled in the schools of Porto, Portugal. Time spent watching TV was collected by self-administered questionnaires and dietary intake was evaluated using a food frequency questionnaire. Included in the analysis were 1436 adolescents. Results: Spending more than 120 min per day watching TV was significantly associated with higher intake of total fat and polyunsaturated fat and with lower intake of magnesium, in both sexes. Additionally, in girls, spending more than 120 min per day watching TV was associated with lower intake of complex carbohydrates, fiber, total vitamin A, folate, vitamin C, calcium, iron, phosphorus, and potassium. In boys, higher intake of saturated fat and cholesterol was found among those spending more time watching TV. Conclusions: We found that television viewing is associated with higher consumption of foods containing more fats and sugars and a lower consumption of fruits and vegetables. Consequently, adolescents who watched more television had a higher intake of total fat and polyunsaturated fat and a lower intake of minerals and vitamins. This dietary behavior among adolescents may have long-term health implications, not only limited to obesity.